Integrasi Nilai-nilai Islam dalam Pembelajaran Matematika : (Studi Kasus MTs Putri Al-Ishlahuddiny Kediri) - Puspita Faadhilaha, Destysara; Pardi, M. Habib Husnial; Evendi, Erpin (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to understand the Islamic values ​​integrated into Mathematics learning at MTs Putri Al-Ishlahuddiny Kediri, and to understand how the integration method is. Using a qualitative approach with a case study type, data was collected through observation, interviews, and documentation. The results of the study indicate that Islamic values ​​such as praying before studying, fairness, and helping each other are applied in Mathematics learning. The value of gratitude is instilled to increase motivation and academic achievement, while fairness and social care encourage the creation of an inclusive and collaborative learning environment. The integration of these values ​​is carried out through teaching that links the concept of Mathematics with Islamic teachings, as well as the preparation of evaluation questions with an Islamic concept. For example, in the material on linear equations, the teacher uses examples that reflect justice. Thus, the integration of Islamic values ​​in Mathematics learning at this madrasah contributes positively to the development of Islamic character.